CHALLENGES AND SOLUTIONS TO IMPROVING TEACHER COMPETENCE IN DISTANCE LEARNING VIA ZOOM, VIDEO, AND GOOGLE MEETING - Huriyah, Huriyah; Begum, Dilara (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: The COVID-19 pandemic significantly impacted education in Indonesia, leading to a shift to distance learning to prevent the virus's spread in schools and madrasahs. Purpose: This study aims to improve teachers' competence in distance learning by utilizing Zoom, video, and Google Meeting. The research is based on a two-day workshop for teachers with more than two years of experience at Madrasah Tsanawiyah (MTs) Insan Saleh. Method: Using a qualitative approach with a phenomenological method, data was collected through observation, interviews, and documentation. Result: The workshop findings show that teachers and staff who attended gained a strong understanding of using modern technology for distance learning. Initially, there were technical challenges, but these were promptly addressed with training and hands-on support from the instructors. As a result, teachers were able to effectively use Zoom, Google Meeting, and video for teaching, improving both their confidence and their students' engagement. Conclusion: The study concludes that such workshops are an effective strategy to enhance teachers' digital competencies, helping them adapt to distance learning and ensure high-quality education despite technological challenges.